MODEL PENGEMBANGAN LITERASI INFORMASI DI PERPUSTAKAAN SEKOLAH - Mashuri, Ilham (STAIN Ponorogo, 2014)
Abstract: Information literacy as continuing agenda has given school library to develop its facilites. This articleÂ tries to describe howÂ school libraries develop IL models. With IL, librarians will study more how to use informations resources increasing fast. For userâs, IL will give skills to study for long life, he will be able to understand the need of information, how to fnd, manage, dan use for daily life.Key word: Information Literacy Models, Information Literacy, School library.